O Palácio da Justiça de Pernambuco: da pedra fundamental à inauguração (1924-1930). - Aguiar, Carla Romeiro Nanes de (2023)
The present work is intended for the production of an illustrated e-book, with an approach on the construction of the Palace of Justice of Pernambuco, a monumental building located in the surroundings of Republic Square, with sumptuous architecture in eclectic style, fruit of the joint work of renowned professionals, which is reflected in the grandeur of its façade and in the artistic work of its internal environments. The work started in 1924 and completed in 1930 is part of the context of major transformations that occurred in the modernization process of the city of Recife, which gave rise to demolitions of old buildings for the opening of avenues and construction of new buildings, implementation of sanitation measures, water and electricity supply. The research methodology involves the comparison of sources obtained in academic repositories, public archives, books, magazines and newspapers, related to the theme studied, aiming at understanding peculiar aspects of the time, in which the municipality was engaged in the national feeling of Europeanization as a synonym of progress and modernity, at the same time that it lacked infrastructure to encompass the population that migrated from the countryside to the city in search of work and subsistence. The product is aimed at the general public, interested in knowing the material cultural heritage of the city of Recife.